Pulmonary Hypertension and Pregnancy - Siromakha, S. O.; Davydova, Yu. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Pregnancy in patients with any type of pulmonary hypertension (PH) is associated with significant morbidity and mortality. That is why pulmonary artery hypertension (PAH) is a contraindication to pregnancy and belongs to class IV maternal cardiovascular risks. Maternal mortality rates for pulmonary (especially arterial) hypertension remain high even in the era of specific therapy, in particular, it reaches 12-30% in patients with PAH, 36% in Eisenmenger syndrome and up to 56% in secondary PH. Perinatal effects in such patients are also unfavorable, with high rates of fetal loss, premature birth and miscarriage. Multidisciplinary team of specialists of the National Amosov Institute of Cardiovascular Surgery and Institute of Pediatrics, Obstetrics and Gynecology named after acad. O. M. Lukianova has been providing medical support to such women for 7 years, using modern recommendations and wide experience. Overall, 39 pregnant and parturient women with PH were admitted to the clinic of the National Amosov Institute of Cardiovascular Surgery in the period from December 2013 to October 2020. Patients with PH were assigned to group II (n=24), and those with PAH (8 women) and acute PH (7 women) were assigned to group I. A total of 20 cardiac surgeries were performed. Patients with acute PH (n=6) underwent operations with cardiopulmonary bypass, those with critical mitral valve stenosis had “closed” off-pump surgery, and also there was one case of ECMO system implantation in patient with dilated cardiomyopathy (CMP). Endovascular operations (n=4) involved occluder implantation to patent ductus arteriosus (PDA), implantation of a cardioverter-defibrillator, cardiac resynchronization therapy with pacemaker (CRT-P) and cava-filter insertion. Early (n=1) and late (n=1) maternal mortality rates were 2.6% each. Perinatal loss (n=5) was 12.8%. The main goal at the preconception stage in patients with PH is to eliminate causative factors, and, if it is impossible (idiopathic, familial PAH, Eisenmenger syndrome, etc.), to avoid pregnancy. Patients who become pregnant should be informed of the high risk of pregnancy and discuss abortion, regardless of the WHO FC or other predictive markers. At prolongation of pregnancy careful clinical monitoring, by pregnancy heart team members is strongly recommended. Multidisciplinary support of pregnant women with PH is the cornerstone of a successful treatment strategy for such patients. The professional association of obstetric risk specialists, cardiologists, interventionists, neonatologists, and cardiac surgeons significantly increases the chances of a PH patient for safe delivery and giving birth to a healthy baby.